2016
DOI: 10.1007/s11999-016-5006-x
|View full text |Cite
|
Sign up to set email alerts
|

What is the Intraarticular Concentration of Tobramycin Using Low-dose Tobramycin Bone Cement in TKA: An In Vivo Analysis?

Abstract: Background Antibiotic-impregnated bone cement has increased in popularity as an effort to reduce the risk of infection in high-risk TKAs. However, limited data has been reported regarding antibiotic levels achieved when using tobramycin-impregnated bone cement after implanting total knee components. Questions/Purposes We asked: (1) What is the tobramycin serum and knee intraarticular levels in patients undergoing primary TKA using tobramycin cement? (2) What is the intraarticular tobramycin level for patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In one study[ 27 ], the revision TKAs were done because of previous infection. Four of the studies did not report such data on the patient population used[ 19 , 20 , 23 , 26 ]. In all of the studies, systemic antibiotics were used in conjunction with AIBC to facilitate recovery and prevent reinfection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In one study[ 27 ], the revision TKAs were done because of previous infection. Four of the studies did not report such data on the patient population used[ 19 , 20 , 23 , 26 ]. In all of the studies, systemic antibiotics were used in conjunction with AIBC to facilitate recovery and prevent reinfection.…”
Section: Resultsmentioning
confidence: 99%
“…Vrabec et al[ 23 ] described that local concentrations of antibiotics from AIBC not only had supratherapeutic concentrations in the joint fluid, but also achieved therapeutic concentrations locally within the first 48 h postoperatively. Systemic antibiotics, on the other hand, only achieved subtherapeutic levels locally, not in the joint fluid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some American authors propose antibiotic-loaded cement prophylaxis for patients at high risk, eg, those with immunosuppression, infl ammatory cause of arthritis, or diabetes. 54 Vrabec et al, 55 in a study of low-dose tobramycin-loaded cement used for primary total knee arthroplasty, found a peak median intra-articular tobramycin concentration of 32 mg/L at 6 hours, declining to 6 mg/L at 48 hours with all serum levels 0.3 mg/L or less (unmeasureable) at similar time points.…”
Section: Low-dose Cementmentioning
confidence: 99%
“…During surgical management of acute septic arthritis with concomitant osteomyelitis, antibiotic impregnated cement (AIC) may be used both as a spacer and to control long-term joint infections [19] . Studies show that AIC leads to local concentrations above the minimum inhibitory concentration for most pathogens, whereas systemic concentrations remain relatively below levels associated with nephrotoxicity [20] , [21] , thus conferring an advantage over intravenous antibiotic administration.…”
Section: Introductionmentioning
confidence: 99%